2007
DOI: 10.1016/j.bbrc.2007.06.165
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of muscleblind-like proteins differs in differentiating myoblasts

Abstract: Muscleblind-like (MBNL) proteins are believed to be regulators of myogenesis and are implicated in myotonic dystrophy. While Drosophila melanogaster muscleblind is required for terminal muscle differentiation, mammalian MBNL3 functions as an inhibitor of myogenesis. In this study, we analyzed the expression pattern of MBNL3 in different adult mouse tissues and tissue culture cells. MBNL3 transcript is enriched in the lung, spleen, and testis and not in heart and skeletal muscle. By western blotting, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…MBNL paralogs differ considerably in terms of function and expression level during embryonic and postnatal development ( 12–18 ). While MBNL1 is the major MBNL family member in adult skeletal muscles and governs myoblast differentiation, MBNL3 is mostly present at early stages of development as well as in the adult placenta, spleen and lung ( 15 , 19 ). MBNL1 is partially compensated by upregulation of MBNL2 but not by MBNL3 ( 7 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…MBNL paralogs differ considerably in terms of function and expression level during embryonic and postnatal development ( 12–18 ). While MBNL1 is the major MBNL family member in adult skeletal muscles and governs myoblast differentiation, MBNL3 is mostly present at early stages of development as well as in the adult placenta, spleen and lung ( 15 , 19 ). MBNL1 is partially compensated by upregulation of MBNL2 but not by MBNL3 ( 7 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining MBNL transcript levels have revealed distinct patterns of expression for MBNL1, MBNL2, and MBNL3 during development and in the adult mouse. (4)(5)(6) These findings suggest that MBNL1, MBNL2, and MBNL3 may display distinct cellular functions in different tissues. Knowledge about protein expression patterns in the adult animal can provide insights into a protein's physiological function.…”
Section: Introductionmentioning
confidence: 86%
“…(8) The expression level of MBNL1 remains unchanged during muscle differentiation. (6,9) However, MBNL1 rapidly redistributes from the nucleus to the cytoplasm in cultures of primary human myoblasts executing the muscle differentiation program. (9) These results prompted us to examine the distribution and localization of MBNL3 in myogenic cells.…”
Section: Lee Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, MBNL1 is expressed mainly in adult skeletal muscle, heart, brain, intestine, kidney, liver, lung, and placenta; a similar expression pattern is reported for MBNL2, although the level of expression in skeletal muscle is not as high as MBNL1. By contrast, MBNL3 expression occurs mainly in the placenta (Fardaei et al , 2002; Kanadia et al , 2003 b ; Lee, Squillace & Wang, 2007; Miller et al , 2000). In addition to these studies with adult tissue samples, experiments with human and mouse myoblasts have also confirmed temporal changes in the pattern of expression of MBNL proteins throughout muscle development, which are species‐specific (Holt et al , 2009; Miller et al , 2000).…”
Section: Expression Of Muscleblind In Terminally Differentiating mentioning
confidence: 96%